DLGS97/SAP97 is developmentally upregulated and is required for complex adult behaviors and synapse morphology and function - Mendoza Topaz, Carolina (2008)
The synaptic membrane-associated guanylate kinase (MAGUK) scaffolding protein family is thought to play key roles in synapse assembly and synaptic plasticity. Evidence supporting these roles in vivo is scarce, as a consequence of gene redundancy in mammals. The genome of Drosophila contains only one MAGUK gene, discs large (dlg), from which two major proteins originate: DLGA [PSD95 (postsynaptic density 95)-like] and DLGS97 [SAP97 (synapse-associated protein)-like]. These differ only by the inclusion in DLGS97 of an L27 domain, important for the formation of supramolecular assemblies. Known dlg mutations affect both forms and are lethal at larval stages attributable to tumoral overgrowth of epithelia. We generated independent null mutations for each, dlgA and dlgS97. These allowed unveiling of a shift in expression during the development of the nervous system: predominant expression of DLGA in the embryo, balanced expression of both during larval stages, and almost exclusive DLGS97 expression in the adult brain. Loss of embryonic DLGS97 does not alter the development of the nervous system. At larval stages, DLGA and DLGS97 fulfill both unique and partially redundant functions in the neuromuscular junction. Contrary to dlg and dlgA mutants, dlgS97 mutants are viable to adulthood, but they exhibit marked alterations in complex behaviors such as phototaxis, circadian activity, and courtship, whereas simpler behaviors like locomotion and odor and light perception are spared. We propose that the increased repertoire of associations of a synaptic scaffold protein given by an additional domain of protein-protein interaction underlies its ability to integrate molecular networks required for complex functions in adult synapses.